2012
DOI: 10.1093/infdis/jis532
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerable Groups Within a Vulnerable Population: Awareness of the A(H1N1)pdm09 Pandemic and Willingness to Be Vaccinated Among Pregnant Women in Ivory Coast

Abstract: Gaps in knowledge about the influenza pandemic and vaccine highlight the challenges of pandemic preparedness in poorer countries, where substantial disparities in education and media access are evident.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 20 publications
1
18
0
6
Order By: Relevance
“…Despite limited vaccine knowledge, most primary caregivers said they would get an influenza vaccine if available for free, although this proportion varied by site. While studies of vaccine acceptability among primary caretakers in the community are limited, willingness to accept influenza vaccine in this study was similar to acceptability observed among healthcare workers in Kenya16 and Cote d'Ivoire17 and higher than acceptability observed among pregnant women in Cote d'Ivoire18 during the 2009 influenza A (H1N1) pandemic. We did not explore how clinician recommendations, which have been shown to influence vaccination attitudes and practices,19 might affect willingness to receive influenza vaccine in this population.…”
Section: Discussionsupporting
confidence: 68%
“…Despite limited vaccine knowledge, most primary caregivers said they would get an influenza vaccine if available for free, although this proportion varied by site. While studies of vaccine acceptability among primary caretakers in the community are limited, willingness to accept influenza vaccine in this study was similar to acceptability observed among healthcare workers in Kenya16 and Cote d'Ivoire17 and higher than acceptability observed among pregnant women in Cote d'Ivoire18 during the 2009 influenza A (H1N1) pandemic. We did not explore how clinician recommendations, which have been shown to influence vaccination attitudes and practices,19 might affect willingness to receive influenza vaccine in this population.…”
Section: Discussionsupporting
confidence: 68%
“…perceiving the likelihood of getting the disease as low (HCP 4/117 [ 43 , 73 75 ]; Pregnant 1/35 [ 76 ]; Elderly 1/62 [ 77 ]; Public 9/191 [ 68 , 72 , 78 84 ]) and perceiving the severity of the disease as low (HCP 8/117 [ 44 , 85 91 ]; Pregnant 3/35 [ 92 94 ]; Chronic 3/45 [ 58 , 95 , 96 ]; Children 2/18 [ 97 , 98 ]; Elderly 4/62 [ 96 , 99 101 ]; Public 16/191 [ 65 , 71 , 72 , 81 , 83 , 99 , 102 111 ]). Additionally, perceiving oneself as less susceptible to the disease decreased the uptake of the influenza vaccine in 23 studies (HCP 4/117 [ 42 , 112 114 ]; Pregnant 3/35 [ 115 118 ]; Chronic 1/45 [ 95 ]; Children 1/18 [ 119 ]; Elderly 1/62 [ 99 ]; Public 11/191 [ 99 , 107 , 108 , 120 128 ]).…”
Section: Resultsmentioning
confidence: 99%
“…The studies were conducted between 2010 to 2017. There were four studies from Africa (Malawi [ 22 ], Ethiopia, Ghana, Uganda, Laos [ 23 ], Gambia [ 24 ], Ivory Coast [ 25 ]), four from the Americas (El Salvador, Peru [ 26 , 27 ], Nicaragua [ 28 , 29 ]), two from Eastern Mediterranean region (Pakistan [ 30 ], Morocco [ 31 ]) and one from South-East Asia (India) [ 32 ]. Ten studies included pregnant or recently pregnant women and three studies included HCPs as respondents for the study.…”
Section: Resultsmentioning
confidence: 99%